Responding to the crisis: food co-operatives and the solidarity economy in Greece - Rakopoulos, Theodoros (Anthropology Southern Africa (Anthropology Southern Africa), 2013)
This article discusses a case of popular social response to imposed austerity and recession in Greece. It focuses on the anti-middleman movement in an Athens suburb. It also addresses the broader picture of the current Greek crisis, explaining how participants in this grassroots response extend their activity beyond food distribution, beginning to imagine modes of economic conduct and interaction different from those currently dominant in Greece. I explore their efforts to turn the food market they have established in Athens into a formal co-operative which links consumers in their neighbourhood directly to selected farmers through bonds of solidarity, and to work with others to create a network of similar co-operatives which will span the whole country. I argue that their endeavours strongly resemble the co-operativism and practical socialism advocated by important social theorists such as Mauss and Polanyi, and suggest that it may be important for the young activists in Athens to learn more about their ideas.
Anthropology
Keywords: Greece; Greek crisis; MAUSS; Marcel; 1872-1950; anthropological research; anti-middleman movements; economic development; financial crises; financial crisis; food co-operatives; food industry; horizontal co-operative networks; recessions; solidarity economy; sovereign debt crisis

Towards a human economy: reflections on a new project - Sharp, John (Anthropology Southern Africa (Anthropology Southern Africa), 2013)
The University of Pretoria's Human Economy project began at the end of 2010. To date it has involved eighteen post-doctoral fellows, drawn from around the world, and eight doctoral candidates, all from Africa. This paper reviews the project's progress, drawing attention to how its participants have come to construe the notion of a 'human economy' and the main social theorists on whom they have drawn in doing so. The development of our thinking regarding a human economy is explained by reference to the two edited volumes, comprising contributions from all the post-doctoral fellows, which will be published in the near future. Challenges for future research are considered in the final part of the paper.
Anthropology
Keywords: MAUSS; Marcel; 1872-1950; South Africa; University of Pretoria; doctoral degree; economic development; human economy; market exchange; mutuality; plural economy; reform; revolution; social development; social sciences

Interests, Resources and Status: The Distribution of Income, Work and Authority in the Family in a Northern Hungarian Village - Sárkány, Mihály (Acta Ethnographica Hungarica, 2013)
The author deals with two interconnected features of contemporary Hungarian rural family life from a historical perspective based on fieldwork carried out in Varsány in the early 1970s and between 2000 and 2005. The first is the intertwining of the lives of successive generations of families in a period when other segments of Hungarian society were becoming more individualistic. This case puts into question whether economic models of the direction of the flow of goods between generations (linear, altruistic or exchange models) are applicable for this situation. The author suggests that Polányi's ideas may be of help in understanding this phenomenon. The second is the balance of genders within families. Tatjana Thelen, who did fieldwork in another Hungarian village, Mesterszállás, pointed out a decline in the status of women. She holds the Hungarian policy of privatisation and reprivatisation responsible for it, which followed the great socio-economic and political change from socialism to capitalism in 1990. As a similar decrease in the status of women did not occur in Varsány, the author argues that other factors also should be taken into consideration for analysing such situations, like the role of commuting, education, and women's share in landed property.
Anthropology
Keywords: Hungary; authority; distribution (economic theory); families; gender; generation; income distribution; research; rural family; transfer of income; work